Genome-wide characterization and expression analysis of the JRL gene family in response to hormones and abiotic stress in tomato (Solanum lycopersicum L.) - Hui Li; Hongling Hu; Lina Cao; Yue Zhuo; Liting Wang; Hui Ma; Ming Zhong (PeerJ)
Jacalin-related lectins (JRLs), a newly discovered subfamily of plant lectins, play an important role in plant growth and development and abiotic stress response. However, in the most important model and economic plant, the tomato, little is known about this gene family. Here, we conducted a genome-wide identification and characterization of the JRL gene family in tomato. A total of eight JRL gene family members (SlJRL1–SlJRL8) were identified based on the tomato genome through bioinformatics analyses, which were unevenly distributed on four chromosomes. Chromosomal localization revealed four pairs of tandemly duplicated genes. Genome collinearity analyses showed that tomato JRL genes were more closely related to Arabidopsis than to rice and maize. Phylogenetic analysis showed that tomato JRL could be divided into seven subgroups, and members within each subgroup shared similar gene structures and conserved motifs. Promoter analysis revealed abundant cis-acting elements associated with stress-responsive and phytohormone-responsive. Finally, real-time quantitative polymerase chain reaction (qRT-PCR) was used to analyze the expression profile of SlJRL gene under various plant hormone and abiotic stress treatments. The results show that the SlJRL gene family exhibits tissue-specific expression patterns and responds to a variety of hormonal and stress conditions. This study systematically analyzed the genomic characteristics of tomato JRL family. Our results lay the foundation for further studies on the biological functions of tomato JRL genes.